Annual report of the trustees of the Perkins Institution and Massachusetts School for the Blind upon the work of the instruction of the adult blind at their homes : presented to the State Board of Education. - Perkins Institution and Massachusetts School for the Blind, issuing body. (Tufts University. Tisch Library., 2025)
A brief report dealing only with the instruction of the adult blind in their homes. Differs from the regular Annual report of the trustees.